Work situation of patients with stroke who have returned to work: a scoping review protocol - Huixiao Wang; Yanping Si; Guangliu Wu; Jinpei Wen; Mingying Yang (BMJ Open)
Introduction The incidence of stroke in working-age adults is increasing. Many patients face cognitive, emotional and physical impairments and their subsequent influences on returning to work. An increasing number of studies have been conducted on the transformation from unemployment to returning to work. The criteria for returning to work only used the ‘working yes/no’ as the primary outcome. Although some researchers have investigated the characteristics of patients with stroke who have returned to work, there is a paucity of evidence regarding the work situation. This scoping review aimed to examine and map the work situation of patients with stroke who have returned to work.Methods and analysis This study will be based on the Joanna Briggs Institute Reviewers’ Manual for scoping reviews. A systematic literature search will be conducted using related medical subject headings and keywords on the work situation of patients with stroke who have returned to work. Relevant publications will be searched using 17 data sources, including grey literature sources, published in English or Chinese between 1957 and 2022. None of the articles will have restrictions on the data sources or study designs. The study selection and search results will be reported and presented according to the Preferred Reporting Items for Systematic Review and Meta-Analyses extension for scoping reviews flow diagram. The results will be presented in a table format based on the data extraction tool.Ethics and dissemination This study is exempted from a medical ethical review. This scoping review addresses the knowledge gap by identifying and synthesising the work situation of patients with stroke who have returned to work, which will provide helpful information for various stakeholders. This scoping review will be submitted and published in a peer-reviewed scientific journal.